(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The cable revolution in India post 1991 was by no means a small achievement in democratizing the viewers ability to demand content from producers. At the click of a remote the audience was at home with global content with a plethora of choices in multiple languages. But what this largesse hid in plain sight was the systematic erasure of the local content from the screens. By local here I mean grassroots content from the communities. In this paper I study the local cable television channels in Assam by taking one such operator base channels called V&S network. This operated within a community or at best within a district for example and produced programming that was relevant to the immediate masses. The system of operation was a highly localized form of cooperative news and content gathering. This sort of media is termed as truly local which caters to the sections of the neighborhood. Despite legal hurdles local cable channels have thrived and survived although precariously.